Pengaruh Kegiatan Pesantren Ramadhan terhadap Pembentukan Karakter Peserta Didik di SMPIT Al Mumtaz Candelekan Cikande Jayanti Tangerang - Solihin Solihin; Ujang Saefuddin Rosyid; Robiatul Adawiyah (LPPM STAI La Tansa Mashiro, 2026)
This study aims to examine the influence of Ramadan pesantren activities on the character development of students at SMPIT Al Mumtaz Candelekan Cikande Jayanti Tangerang. The research employs a qualitative approach with a case study design. Data were collected through several techniques, including observation, in-depth interviews, and documentation. The data were then analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of Ramadan pesantren activities is carried out in a structured and well-organized manner, encompassing various activities such as worship, Islamic studies, and moral development. In practice, students’ character formation occurs through habituation, role modeling, and the support of a religious environment. These processes contribute positively to the enhancement of students’ religiosity, discipline, sense of responsibility, and social awareness. Overall, this study not only provides theoretical contributions to the development of pesantren-based character education but also offers practical references for educational institutions in designing more effective Ramadan programs.